From Load Estimation to Performance Estimation—From Model-Scale Test to Full-Scale Test: With Special Interest in Asian Region - Tamura, Yukio; Nishijima, Kazuyoshi; Matsui, Masahiro; Phuc, Pham Van; Yang, Qingshan (Frontiers in Built Environment, 2017)
This paper first discusses the current status of natural-hazard-induced disasters, with special focus on devastating wind-related disasters in the Asian region. The importance of the combined effects of wind and water hazards, the importance of performance of cladding and components in wind resistant design of buildings, and deterioration of metal roofing systems of long-span structures mainly caused by fatigue of fixing joints due to daily solar heating effects are demonstrated. Some human errors caused by lack of attention to aerodynamic and structural behaviors are also indicated. Then, psychological impacts and social impacts are discussed, and common underestimation of social impacts of wind-induced disasters on society is pointed out. The main reason for repeated wind-induced damage is lack of information on the real performance of claddings, components and main frames under wind actions. The demand and necessity for full-scale tests are emphasized, aiming to check the performance of building and structural systems under realistic and controlled conditions of extremely strong actions of wind, rain, snow, fire, solar heating and so on. Finally, the academic and social significance of the full-scale storm simulator is discussed.